2020
DOI: 10.1364/boe.391720
|View full text |Cite|
|
Sign up to set email alerts
|

Optical properties of PlatSil SiliGlass tissue-mimicking phantoms

Abstract: In this work, we revise the preparation procedure and conduct an in depth characterization of optical properties for the recently proposed silicone-based tissue-mimicking optical phantoms in the spectral range from 475 to 925 nm. The optical properties are characterized in terms of refractive index and its temperature dependence, absorption and reduced scattering coefficients and scattering phase function related quantifiers. The scattering phase function and related quantifiers of the optical phantoms are fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Our experimental setup (Figure 1), designed for both transmission and reflection/backscattering geometries, employed a continuous wave near-infrared laser (850 nm, 15 mW). The laser illuminated silicone-based phantoms, simulating turbid media with microscale SiO2 particles [7], characterized by a scattering coefficient (µs = 6 mm-1) and anisotropy factor (g = 0.9) [8]. For dynamic target simulation, an electronic ink (E-ink) display [9] was used, positioned behind the phantom to display (flash) various MNIST dataset characters and images.…”
Section: Methodsmentioning
confidence: 99%
“…Our experimental setup (Figure 1), designed for both transmission and reflection/backscattering geometries, employed a continuous wave near-infrared laser (850 nm, 15 mW). The laser illuminated silicone-based phantoms, simulating turbid media with microscale SiO2 particles [7], characterized by a scattering coefficient (µs = 6 mm-1) and anisotropy factor (g = 0.9) [8]. For dynamic target simulation, an electronic ink (E-ink) display [9] was used, positioned behind the phantom to display (flash) various MNIST dataset characters and images.…”
Section: Methodsmentioning
confidence: 99%
“…The tissue phantoms were prepared from SiliGlass according to a slightly modified recipe of Sekar et al. 19 , 20 The substrate is platinum-cured silicon rubber (PlatSil ® SiliGlass), which is polymerized from two liquid parts, namely part A and part B. Therefore, it can reap the benefits of liquid phantoms such as easy customization of each optical layer by adding small quantities of absorber or scatterer.…”
Section: Methodsmentioning
confidence: 99%
“…An interested reader can find more information in Refs. 19 and 20 . First, the absorber and part A were mixed in a disposable plastic cup for 10 min using a magnetic stirrer and a glass rod.…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of the required parameters directly influences the accuracy of the calculated optical properties. Recently, we have proposed a simple approach to measure the refractive index of polystyrene microspheres 8 . We have found that the most appropriate value for the microspheres is provided by Nikolov et al 6 , although a significant number of publications dealing with turbid phantoms refer to the refractive index of Ma et al 7 .…”
Section: Phantom Protocol Feature Descriptionmentioning
confidence: 99%